2021
DOI: 10.36909/jer.14605
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Suitability of Reclaimed Asphalt Pavement Aggregate (RAPA) in Hot Mix Asphalt Production

Abstract: The main objective of this study was to evaluate the suitability of recycled asphalt aggregate with fresh aggregate in hot mix asphalt production by using experimental laboratory investigation. Also, Non-probable sampling techniques were adopted to collect a sample. The engineering properties of extracted Reclaimed asphalt pavement aggregate and the fresh crushed aggregate were identified based on standard specification before starting the Marshall Mix design, Then the Marshall Stability test was conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Low flow values may suggest a mix has more voids and insufficient asphalt binder, which makes a crack mixture brittle. High flow values, on the other hand, show that the mix contains a high amount of asphalt binder that fills all voids and affects the resistance to permanent deformation under traffic [5]. The flow of the RAPA partially replaced content is higher than the flow of the CSA mix and the flow rises steadily over time.…”
Section: Relationship Between Flow and Rapa Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Low flow values may suggest a mix has more voids and insufficient asphalt binder, which makes a crack mixture brittle. High flow values, on the other hand, show that the mix contains a high amount of asphalt binder that fills all voids and affects the resistance to permanent deformation under traffic [5]. The flow of the RAPA partially replaced content is higher than the flow of the CSA mix and the flow rises steadily over time.…”
Section: Relationship Between Flow and Rapa Contentmentioning
confidence: 99%
“…Although Pakistan has emerged as one of the world's leading road-building nations, many of its roads are deteriorating or approaching the end of their useful lives [3]. In Ethiopia, traditional disposal practices involve sacrificing old asphalt layers by discarding them as garbage instead of replacing them with new asphalt [5]. WPB and RAPA are increasingly employed for pavement rehabilitation worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the test results, they found that the highest Marshall stability value was obtained for a mix containing 30% RAP content [18]. The suitability of RAP in HMA production with varied RAP contents from 5 to 65% by weight of crushed aggregates was studied and concluded that the optimum replacement of RAP aggregates up to 45% with crushed aggregates satisfied the requirements of Ethiopian Roads Authority (ERA), Pavement Design Manual (2013) and Asphalt Institute Manual Series [19]. Marshall stability and flow values were improved as the addition of RAP content was increased and a study reported that the highest stability of 15.1kN was observed for the mix containing 75% RAP with 4% binder content [20].…”
Section: Rap Replacement As MIX In Wearing Course Layer Of Bituminous...mentioning
confidence: 99%